2023
DOI: 10.3389/fpubh.2023.1155999
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation and intrinsic capacity among left-behind older adults in rural China: The chain mediating effect of perceived stress and health-promoting behavior

Abstract: BackgroundStrengthening and maintaining the intrinsic capacity (IC) of the older adults is the key to preventing and delaying disability and promoting healthy aging.ObjectiveThis study explores the relationship between social isolation, perceived stress, health promotion behavior, and IC of the left-behind older adults in rural areas and analyzes the chain mediating effect of perceived stress and health promotion behavior among social isolation and IC.MethodsFrom March 2021 to May 2022, a multi-stage sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Individuals' perceived stress affects their health behaviors and health outcomes. 31 , 32 , 33 Individuals with high stress levels tend to have an unhealthy lifestyle, such as smoking, compared to those with low stress levels. 33 However, unlike stress generally being associated with negative health behaviors, 31 , 32 , 33 we found that higher stress levels were associated with a higher intention for lung cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals' perceived stress affects their health behaviors and health outcomes. 31 , 32 , 33 Individuals with high stress levels tend to have an unhealthy lifestyle, such as smoking, compared to those with low stress levels. 33 However, unlike stress generally being associated with negative health behaviors, 31 , 32 , 33 we found that higher stress levels were associated with a higher intention for lung cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…Social support can buffer the harmful impacts of stress on physical and mental health to maintain individuals’ well-being [ 70 ]. Previous studies revealed that social networks have broader impacts on many health outcomes, such as physical, cognitive, psychological, and overall health [ 71 ]and higher levels of social isolation were positively correlated with lower intrinsic capacity [ 72 ]. Given the considerable social relationship of older adults may change over time due to the relocation of children, relatives, or friends; and death or function limited among social networks [ 73 ].…”
Section: Discussionmentioning
confidence: 99%